The Design Of Information Systems Person With Disabilities At The Department Of Social Welfare The Province Of Lampung - Bobby Bachry (Prosiding International conference on Information Technology and Business (ICITB), 2018)
The departement of social welfare the province of Lampung is a government agency engaged in the field of social welfare, which has the objective to restore the condition or health of physical, mental and social so that it can survive in fair and good in the life of society. The department of social welfare the province of lampung is divided into : program development, development rehabilitation, development assistance and community development program development social. Currently social services do not yet have a good system in processing the data, the rehabilitation of persons with disabilities. The development of the information system of persons with disabilities by using the waterfall method, the stages of the stages are carried out to analyze a running system design and implementation. With the data information system of persons with disabilities is expected to provide accurate information regarding the number of persons with disabilities in the province of Lampung in the decision making. Keywords: The Department Of Social Welfare, Disabilities, Waterfall, Information Systems